2004
DOI: 10.1097/01.hjr.0000129743.53464.c0
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability decreased by coronary artery surgery has no prognostic value

Abstract: In contrast to the strong prognostic potential of HRV in patients with MI, decreased HRV has no prognostic significance in patients who have undergone CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Reduced HRV has been reported also in individuals who have undergone CABG; in these patients, anyway, the abnormal HRV has controversial prognostic significance [8,28], as the autonomic effects of an increased sympathetic activity during and after surgery may be partly balanced by the long-term effects of revascularization of ischemic viable myocardial segments. In patients who have undergone valvular heart surgery, very few data exist to evaluate long-term prognostic relevance of a reduced HRV [11], and no data exist to evaluate if reduced HRV could have a clinical impact in the short-term, soon after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced HRV has been reported also in individuals who have undergone CABG; in these patients, anyway, the abnormal HRV has controversial prognostic significance [8,28], as the autonomic effects of an increased sympathetic activity during and after surgery may be partly balanced by the long-term effects of revascularization of ischemic viable myocardial segments. In patients who have undergone valvular heart surgery, very few data exist to evaluate long-term prognostic relevance of a reduced HRV [11], and no data exist to evaluate if reduced HRV could have a clinical impact in the short-term, soon after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al (40) found a similar result in their retrospective analysis of the Cardiac Arrhythmia Suppression Trial (CAST). This suggests that HRV may not be a uniform prognostic indicator in all clinical populations (39). It has been proposed that decreased HRV may be the result of increased sympathetic activity during CABG surgery.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…It has been proposed that decreased HRV may be the result of increased sympathetic activity during CABG surgery. However, it is possible that a completely different mechanism is responsible for autonomic denervation in this group (39). diabetes mellitus Impaired autonomic nervous function among patients with diabetes as assessed by HRV has been observed in otherwise healthy adults (41,42), as well as in children (43) and adolescents (41,44).…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) strongly depressed HRV in the time and frequency domain and nonlinear dynamic analysis in many studies [78][79][80][81][82]. While the mechanism underlying depressed HRV after CABG is still unclear, some studies demonstrated a complete recovery of HRV in 2-3 months after CABG [79,81], whereas some failed to demonstrate a recovery even after 6 months of follow up [80].…”
Section: Modification Of Hrv By Interventions and Drugsmentioning
confidence: 99%
“…While the mechanism underlying depressed HRV after CABG is still unclear, some studies demonstrated a complete recovery of HRV in 2-3 months after CABG [79,81], whereas some failed to demonstrate a recovery even after 6 months of follow up [80]. The prognostic significance of this depressed HRV has also been investigated, but no correlation between depressed HRV and prognosis was found [82]. The effect of early reperfusion by thrombolytic agents or interventions after acute MI on HRV parameters has also been investigated [83][84][85][86][87].…”
Section: Modification Of Hrv By Interventions and Drugsmentioning
confidence: 99%